Preparation and characterization of non-viral gene delivery systems with pEGFP-C1 Plasmid DNA - Uğur Karagöz; Mustafa Kotmakçı; Hasan Akbaba; Vildan Bozok Çetintaş; Gülten Kantarcı (Universidade de São Paulo, 2018)
ABSTRACT In recent years, non-viral delivery systems for plasmid DNA have become particularly important. They can overcome the disadvantages of viral systems such as insertional mutagenesis and unpredicted immunogenicity. Some additional advantages of non-viral gene delivery systems are; good stability, low cost, targetability, delivery of a high amount of genetic materials. The aim of the study was to develop novel non-viral nanosystems suitable for gene delivery. Two formulations were developed for this purpose: water-in-oil microemulsion (ME) and solid lipid nanoparticles (SLN). The microemulsion was composed of Peceol, Tween 80, Plurol oleique, ethanol and water. The SLN was consisting of Precirol, Esterquat-1 (EQ1), Tween 80, Lecithin, ethanol and water. Characterization studies were carried out by measuring particle size, zeta potential, viscosity and pH. TEM imaging was performed on SLN formulations. Protection against DNase I degradation was examined. Cytotoxicity and transfection efficacy of selected formulations were tested on L929 mouse fibroblast cells. Particle sizes of complexes were below 100 nm and with high positive zeta potential. TEM images revealed that SLNs are spherical. The SLN:DNA complexes have low toxicity and good transfection ability. All results showed that the developed SLN formulations can be considered as suitable non-viral gene delivery systems.